Third and fourth degree perineal tear audit, NHS Lothian. (18th April 2012) - Penneycard, JM; Cunningham, Y; Love, C
Abstract : Perineal injuries are a recognised complication of vaginal deliveries, with an overall risk of 1%. Although there are many recognised risk factors, it can still be difficult to predict their occurrence. There is however great importance in diagnosing them to allow appropriate management as, if appropriately managed, 60-80% of women will be asymptomatic at 12 months. This audit looked at the incidence and management of third and fourth degree tears occurring in NHS Lothian hospitals May 2009-May 2010. During this period there were 10, 411 deliveries and 293 patients sustaining 3 rd and 4 th degree perineal tears (2.8% of deliveries). 76% of patients sustaining these injuries were primiparous with 62% occurring following a SVD; 49% were 3a. The incidence was thought to be rising in a 2008 audit; this has been re-enforced in this audit with statistical significance (p<0.05). Possible causes were investigated with no increase in mean birth-weight or percentage of instrumental deliveries. Better identification of tears and a seeming reluctance to perform prophylactic RML episiotomies may contribute. 98% of repairs were carried out by an SpR or consultant; 100% in theatre. Documentation of intra- and post-operative antibiotics met standards in the main tertiary hospital but needed improvement in the DGH. Documentation of physiotherapy review and incident reporting also required improvement. As a result a new discharge checklist has come into use and work is going into multi-disciplinary education; not only aimed at management but also prevention and identification.